Measurements of Radon gas Concentration in a Soil at Some Towns in Kassala State - A. Elzain, Abd-Elmoniem; K. Sarn, Adam; M. Mukhtar, Othman; A. Abbasher, Mustafa (Gezira Journal of Engineering and Applied Sciences, 2009)
In this work, radon gas concentration in the soil of some towns in Kassala State in eastern Sudan was measured. To perform this task 206 soil samples were studied randomly. The study was made on: Kassala (90 soil samples), Aroma (40 soil samples), Khashm Algirba (36 soil samples) and Halfa Aljadida city (40 soil samples).  Previously calibrated dosimeters containing solid  state nuclear track detectors  SSNTDs type of CR- 39 were used. The soil- radon gas concentration obtained in Kassala town ranged from 452.10 Bq/m 3 to 7766.89 Bq/m 3 , with an average of (2885.98±419.36) Bq/m 3 . In Aroma town, soil- radon gas concentration ranged from 1942.99 Bq/m 3 to 5727.38 Bq/m 3 , with an average of (3336.89±500.99) Bq/m 3 . While in Khashm  Algirba  town  the  soil  radon  gas  concentration was found  to  be  in  the range  between  807.68  Bq/m 3  and 5227.03 Bq/m 3 with an average of (2169.00 ± 436.99) Bq/m 3 . In Halfa  Aljadida  the soil   -   radon   gas  concentration  values  ranged between 1023.56 Bq/m 3 and 4145.05 Bq/m 3 , with an average of(2106.08±397.40) Bq/ m3 . The  minimum  average  of soil- radon    gas concentration was found  to  be  in Kassala State where the concentration is (2624.49 ± 438.69) Bq/m 3 . It was also found that soil- radon gas concentration increased with depth.